2010
DOI: 10.1063/1.3464485
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast deactivation processes in the 2-aminopyridine dimer and the adenine-thymine base pair: Similarities and differences

Abstract: 2-aminopyridine dimer has frequently been used as a model system for studying photochemistry of DNA base pairs. We examine here the relevance of 2-aminopyridine dimer for a Watson-Crick adenine-thymine base pair by studying UV-light induced photodynamics along two main hydrogen bridges after the excitation to the localized 1 ‫ء‬ excited-state. The respective two-dimensional potential-energy surfaces have been determined by time-dependent density functional theory with Coulomb-attenuated hybrid exchange-correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
8
22
1
Order By: Relevance
“…On the other hand, 11-TD is able to describe the complexity of the interaction of the CT state with several states on its way towards SPT geometries. We compare some key results from both levels of theory with the studies by Samoylova et al 46 and Ai et al 47 In the former study, the vertical/adiabatic excitation energies for the LE states obtained as 4.36 eV/4.00 eV, where the latter matched an earlier experiment. 69 In the present study, we find the two nearly degenerate states with somewhat lower vertical energies of 3.98 eV and 4.08 eV at the 5-XMS level (see Table 1), while their adiabatic energies are lower at 3.43 eV and 3.69 eV, respectively (see Table 4).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…On the other hand, 11-TD is able to describe the complexity of the interaction of the CT state with several states on its way towards SPT geometries. We compare some key results from both levels of theory with the studies by Samoylova et al 46 and Ai et al 47 In the former study, the vertical/adiabatic excitation energies for the LE states obtained as 4.36 eV/4.00 eV, where the latter matched an earlier experiment. 69 In the present study, we find the two nearly degenerate states with somewhat lower vertical energies of 3.98 eV and 4.08 eV at the 5-XMS level (see Table 1), while their adiabatic energies are lower at 3.43 eV and 3.69 eV, respectively (see Table 4).…”
Section: Discussionsupporting
confidence: 64%
“…On the proton transfer side, Samoylova et al 46 identified two CT states as did Ai et al 47 These states, including the upper CT state, are suggested as having a key role to play in the ultrafast relaxation rates. Our 11-TD plots in Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous TEAS and TVAS studies of WC G•C pairs provided compelling evidence for sequential EDPT dynamics. 14 28 which predict that, although bound with respect to potential energy, 22,23,28 A*•T* tautomers are not stable in Gibbs free energy space. This behavior contrasts both theoretical predictions and experimental findings for G•C, which together show that the corresponding G*•C* tautomer can be generated through a twostep EDPT mechanism and is subsequently stable on a timeframe of ≥ 1 ns.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to G•C, theoretical studies have also predicted that both single and/or sequential double EDPT pathways may be active in individual adenine-thymine (A•T) WC pairs after UV excitation. 5,[22][23][24][25][26][27] However, unlike G•C, there is some debate regarding the stability of the imino-enol tautomer pair of A•T resulting from double Hatom transfer 23,28 and whether EDPT is enhanced when A•T is placed in polar solvents. 6 Zhang et al invoked hybrid EDPT pathways to be active in DNA duplexes containing only A•T, 13 Herein, we report the first TEAS and TVAS measurements on a chemically modified A•T WC base pair, solvated in chloroform solution, which eliminates formation of undesired Hoogsteen-type structures.…”
Section: Introductionmentioning
confidence: 99%